Exploring innovation intermediaries in public services: a case study of Malaysia's Smart Card Flagship project. (12th December 2011) - Omar, Aliza Akmar; Mohan, Avvari V.
The paper focuses on the different types of innovation intermediaries in a project serving national interests – the Smart Card Flagship project, a network of public and private organisations formed through policy interventions by the Malaysian Government. An important finding is the formation of intermediaries specifically for the network that, in turn, helps develop linkages between the organisations. Some organisations are found to take on an intermediary role, in addition to their principal role, in the network. Findings also indicate that the quality of the inter-organisational relationships, and the presence of well managed network conditions conducive for innovation activities, effectively ensure the ability of the organisations to intermediate. These findings offer lessons to other developing countries on how public-private partnerships can be effectively leveraged. The case study provides insights on innovation intermediaries in an emerging economy where there is a high level of dependence on foreign sources for technology.